Prognostic significance of Fuhrman grade and age for cancer-specific and overall survival in patients with papillary renal cell carcinoma: results of an international multi-institutional study on 2189 patients - Borgmann, Hendrik; Younsi, Nina; Wagener, Nina; Pahernik, Sascha (World journal of urology, 2017)
Purpose: Because the prognostic impact of the clinical and pathological features on cancer-specific survival (CSS) and overall survival (OS) in patients with papillary renal cell carcinoma (papRCC) is still controversial, we want to assess the impact of clinicopathological features, including Fuhrman grade and age, on survival in surgically treated papRCC patients in a large multi-institutional series .Methods: We established a comprehensive multi-institutional database of surgically treated papRCC patients. Histopathological data collected from 2189 patients with papRCC after radical nephrectomy or nephron-sparing surgery were pooled from 18 centres in Europe and North America. OS and CSS probabilities were estimated using the Kaplan-Meier method. Multivariable competing risks analyses were used to assess the impact of Fuhrman grade (FG1-FG4) and age groups (<50 years, 50-75 years, >75 years) on cancer-specific mortality (CSM). Results: CSS and OS rates for patients were 89 and 81% at 3 years, 86 and 75% at 5 years and 78 and 41% at 10 years after surgery, respectively. CSM differed significantly between FG 3 (hazard ratio [HR] 4.22, 95% confidence interval [CI] 2.17-8.22; p < 0.001) and FG 4 (HR 8.93, 95% CI 4.25-18.79; p < 0.001) in comparison to FG 1. CSM was significantly worse in patients aged >75 (HR 2.85, 95% CI 2.06-3.95; p < 0.001) compared to <50 years.ConclusionsFG is a strong prognostic factor for CSS in papRCC patients. In addition, patients older than 75 have worse CSM than patients younger than 50 years. These findings should be considered for clinical decision making.
Gesehen am 16.05.2018